Presence and Characterisation of Anaemia in Diabetic Foot Ulceration - J. A. Wright; M. J. Oddy; T. Richards (Anemia)
Introduction. Diabetic foot ulceration (DFU) is the commonest cause of severe limb ischaemia in the western world. In diabetes mellitus, anaemia is frequently unrecognized, yet studies have shown that it is twice as common in diabetics compared with nondiabetics. We aimed to assess the incidence of anaemia and further classify the iron deficiency seen in a high-risk DFU patient group. Methods. An observational study was undertaken in a multidisciplinary diabetic foot clinic setting. All patients with DFU attending over a four-month period were included. Anaemia was defined as haemoglobin (Hb) levels <12 g/dL. Iron deficiency was classified according to definitions of AID (absolute iron deficiency) and FID (functional iron deficiency). Results. 27 patients had DFU; 14 (51.9%) were anaemic; two (7.41%) had severe anaemia (Hb < 10 g/dL). No patient had B12 or Folate deficiency. In patients with anaemia, there was significant spread of indices. Only one patient had “textbook” absolute iron deficiency (AID) defined as low Hb, MCV, MCH, and ferritin. Functional iron deficiency (FID) was seen in a further seven patients (25.5%). Conclusion. Anaemia and iron deficiency are a common problem in patients with DFU. With current clinical markers, it is incredibly difficult to determine causal relationships and further in-depth scientific study is required.